Sensorial donor site morbidity after saphenous neurocutaneous flap - GÜNDÜZ, OSMAN HAKAN (TAYLOR & FRANCIS AS, 2005)
Neurocutaneous flaps based on the arterial network around the superficial sensory nerves are popular in soft tissue coverage of the lower extremities, and are usually preferred in reconstruction of the lower leg and foot. Although sacrifice of sensory cutaneous nerves is mentioned as one of their major disadvantages to our knowledge the morbidity in the foot and at the donor site has not been properly investigated. We investigated sensorial morbidity in the foot and at the donor site caused by raising a saphenous neurocutaneous flap in 14 patients by using static two-point discrimination test, Semmes-Weinstein monofilament test, vibration test, and by measuring somatosensory evoked potentials in the twelfth postoperative month. Our results suggest that sensory recovery is good and protective sensation is gained in most patients.
Keywords: Saphenous neurocutaneous flap; sensorial donor site morbidity; NONINNERVATED FREE FLAPS; NEUROFASCIOCUTANEOUS FLAPS; RECONSTRUCTION; FOOT; LEG; MONOFILAMENT; THRESHOLD; SALVAGE; NERVES